2013
DOI: 10.1103/physrevlett.111.100504
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Generation of Quantum Discord via Noisy Processes

Abstract: Quantum systems in mixed states can be unentangled and yet still correlated in a way that is not possible for classical systems. These correlations can be quantified by the quantum discord and might provide a resource for certain mixed-state quantum information processing tasks. Here we report on the generation of discordant states of two trapped atomic ions via Markovian decoherence processes. While entanglement is strictly nonincreasing under such operations, discord can be generated in various forms. Firstl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…The improvement we predict is consistent with the capability of correlated noisy channels to bring about nonclassical features, as in [36]. In conclusion we have discussed how a physical property of photon pairs, namely their frequency correlations, should be taken into account when one studies their use for phase estimation.…”
Section: Resultssupporting
confidence: 60%
“…The improvement we predict is consistent with the capability of correlated noisy channels to bring about nonclassical features, as in [36]. In conclusion we have discussed how a physical property of photon pairs, namely their frequency correlations, should be taken into account when one studies their use for phase estimation.…”
Section: Resultssupporting
confidence: 60%
“…There, particular attention was paid to the existence and robustness of so called decoherence free sub-spaces (DFS) under collective dephasing [25]. Moreover, recent studies [28,29] have shown that collective dephasing could also be used as a resource to generate strong but separable correlations. We note that, due to their promise as a general passive strategy to protect quantum resources from noise, the study of DFS continues to be an active area of research, see [30] for a recent review on the theoretical aspects and [31] for experimental implementations.…”
mentioning
confidence: 99%
“…The physical origin of collective dephasing is left unspecified in the theoretical treatment here. Note that it can, for instance, arise via correlated magnetic field fluctuations for ions [28] or due to interactions with phononic baths in the case of colour centers [23,36,37] (see [38] for additional details regarding such situations).…”
mentioning
confidence: 99%
“…Unlike entanglement, production of discord-like QCs is not demanding since they can be created from classicallycorrelated states via local noise [12][13][14][15][16], a situation forbidding any entanglement to arise. In this respect, a rather spectacular effect that might have profound technological developments is entanglement activation (EA) via discord [17][18][19][20] in a four-partite system.…”
Section: Introductionmentioning
confidence: 99%